Stem Cell Physiology and Cellular Differentiation: Molecular Insights and Therapeutic Potential - Khairullah, Aswin Rafif; Rehman, Saifur; Mustofa, Imam; Pratama, Bima Putra; Martindah, Eny; Ansori, Arif Nur Muhammad; Sukmanadi, Mohammad; Ma’ruf, Ilma Fauziah; Analianasari, Analianasari; Ahmad, Riza Zainuddin; Prihandani, Sri Suryatmiati; Wardhani, Bantari Wisynu Kusuma; et al. (Trends in Sciences, 2026)
Stem cells are unique cells capable of maintaining self-renewal and differentiating into various specialized cell types. These properties make them crucial components in tissue physiology, homeostasis, and regeneration. Stem cell differentiation is regulated through a complex interplay of molecular signaling pathways, transcription factors, microRNAs, and epigenetic mechanisms. Key pathways such as Wnt, Notch, Hedgehog, and BMP/TGF-β play a role in determining cell fate, regulating proliferation, and balancing self-renewal and specialization. Proper regulation ensures that stem cells transition to specific phenotypes in a directed, stable, and physiologically appropriate manner, while disruption of regulation can lead to tissue degeneration or tumors. Understanding these molecular mechanisms paves the way for innovative regenerative therapies. Pluripotent and multipotent cells are used for cell replacement strategies in degenerative diseases, organ injuries, and hematopoietic disorders. iPSCs allow the engineering of a patientʼs own cells to minimize the risk of immunoreactions, while MSCs possess immunomodulatory capabilities and secrete paracrine factors that support endogenous tissue repair. Technologies such as 3D organoid culture, biomaterial scaffolds, and gene editing improve control over differentiation, tissue integration, and therapeutic safety before clinical application. Stem cells and cellular differentiation mechanisms form a solid scientific foundation for the development of modern regenerative therapies. Ongoing research in this area is expected to open new opportunities for tissue function restoration, the treatment of degenerative diseases, and the implementation of safe, effective, and precision therapeutic strategies. HIGHLIGHTS Mechanistic foundations: Core TFs (OCT4/SOX2/NANOG) with epigenetic bivalency, plus pathway crosstalk (Wnt, Notch, Hedgehog, BMP/TGF-β) orchestrate pluripotency and fate decisions/homeostasis. Contextual regulation: Niche cues (ECM, mechanotransduction, hypoxia/HIF-1α) and metabolic reprogramming (glycolysis→OXPHOS) govern transitions among quiescence, activation, and differentiation. Translation & safety: Platforms (2D culture, organoids, co-culture, lineage tracing, xenografts) underpin regenerative applications (heart, CNS, liver) while highlighting safety hurdles (engraftment, off-target differentiation, teratoma risk) and mitigation strategies. GRAPHICAL ABSTRACT